New horizons - Riggs, Kate. (Mankato, MN : Creative Education, 2018)
A fast-paced, high-interest overview of the features, purpose, history, and high-speed capabilities of the New Horizons probe, one of the fastest moving spacecraft in history.
Includes index.
Keywords: Pluto probes; Space probes